The Dark Side of Antibiotics: Adverse Effects on the Infant Immune Defense Against Infection - Shekhar, Sudhanshu; Petersen, Fernanda Cristina (Frontiers in Pediatrics, 2020)
Although antibiotics confer significant health benefits in treating or preventing bacterial infections, an accumulating wealth of evidence illustrates their detrimental effect on host-microbiota homeostasis, posing a serious menace to the global public health. In recent years, it is becoming evident that infants, who are subjected to frequent antibiotic exposures due to their vulnerability to infection, reflect increased susceptibility to a wide spectrum of diseases, including infection, in later life. Antibiotics induce perturbations of the microbiota or dysbiosis, which in turn alters the host immune responses against pathogens. In comparison with adults, antibiotic treatments in infants have disproportionate consequences because the infant microbiota represents an evolving system that is unstable and immature until 2-3 years of age. However, relatively less knowledge is available on how antibiotics affect the infant microbiota and immunity. In this review article, we focus on how antibiotic treatment regimens influence the infant innate and adaptive immunity to pathogens in humans and animal models, and make the host susceptible to infections in later life. There is a critical need to better understand the effect of antibiotics on infant immune function, which may have implications for developing effective prophylactics and therapeutics against diseases in infants and adults.